Robbing the Riches : Capital Flight, Institutions, and Instability - Saxena, Sweta; Cerra, Valerie; Rishi, Meenakshi (Washington, D.C. : International Monetary Fund, 2005)
Capital flight may undermine economic growth and the effectiveness of debt relief and foreign aid. This paper is the first attempt to test whether unsound macroeconomic policies or weak institutions lead to capital flight, using panel data for a large set of developing, emerging market and transition countries. In addition, the paper tests the revolving door hypothesis that links debt accumulation and capital flight, and analyzes the contribution of institutions to several channels in this relationship.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet